Obesity I: Overview and molecular and biochemical mechanisms - Lustig, Robert H; Collier, David; Kassotis, Christopher; Roepke, Troy A; Kim, Min Ji; Blanc, Etienne; Barouki, Robert; Bansal, Amita; Cave, Matthew C; Chatterjee, Saurabh; Choudhury, Mahua; Gilbertson, Michael; et al. (Biochemical pharmacology, 2022)
Obesity is a chronic, relapsing condition characterized by excess body fat. Its prevalence has increased globally since the 1970s, and the number of obese and overweight people is now greater than those underweight. Obesity is a multifactorial condition, and as such, many components contribute to its development and pathogenesis. This is the first of three companion reviews that consider obesity. This review focuses on the genetics, viruses, insulin resistance, inflammation, gut microbiome, and circadian rhythms that promote obesity, along with hormones, growth factors, and organs and tissues that control its development. It shows that the regulation of energy balance (intake vs. expenditure) relies on the interplay of a variety of hormones from adipose tissue, gastrointestinal tract, pancreas, liver, and brain. It details how integrating central neurotransmitters and peripheral metabolic signals (e.g., leptin, insulin, ghrelin, peptide YY3-36) is essential for controlling energy homeostasis and feeding behavior. It describes the distinct types of adipocytes and how fat cell development is controlled by hormones and growth factors acting via a variety of receptors, including peroxisome proliferator-activated receptor-gamma, retinoid X, insulin, estrogen, androgen, glucocorticoid, thyroid hormone, liver X, constitutive androstane, pregnane X, farnesoid, and aryl hydrocarbon receptors. Finally, it demonstrates that obesity likely has origins in utero. Understanding these biochemical drivers of adiposity and metabolic dysfunction throughout the life cycle lends plausibility and credence to the "obesogen hypothesis" (i.e., the importance of environmental chemicals that disrupt these receptors to promote adiposity or alter metabolism), elucidated more fully in the two companion reviews.
Keywords: leptin; Adipocytes; Metabolism; tukové buňky; Obesity; inzulin; Insulin; Energy Metabolism; Hormone receptors; Energy balance; Leptin; Microbiome; Adipose tissue; energetický metabolismus; Humans; Adipose Tissue; obezita; tuková tkáň; lidé